Capturing the final stage of the collapse of cavitation bubbles generated during nanosecond laser ablation of submerged targets. (February 2021) - Long, Jiangyou; Eliceiri, Matthew H.; Wang, Letian; Vangelatos, Zacharias; Ouyang, Yuexing; Xie, Xiaozhu; Zhang, Yongkang; Grigoropoulos, Costas P.
Graphical abstract: Highlights: Bubbles' evolution in three liquids is similar except at the final stage of collapse. The collapse is hindered by the gaseous products inside the bubble in organic liquids. The bubble collapse may affect both the ablation rate and the morphology of ablated areas. Abstract: We observe and study the growth and collapse of cavitation bubbles generated during the pulsed laser ablation of submerged targets in three liquid environments, water, ethanol, and n -butanol, utilizing a stroboscopic shadowgraphy system. The transient images of the final stage of bubble collapse when the bubble volume is at a minimum are captured. Ethanol and n -butanol are subject to cavitation-induced reactions, which produce gaseous products that hinder the implosive collapse of the bubbles. In contrast, laser-produced cavitation bubbles in water achieve the smallest radii at the final stage of collapse, resulting in a sharper increase in localized temperature and pressure that can drive a potential second etching. Our results emphasize the role of the chemical effects of liquids on the implosive collapse of cavitation bubbles, providing a deeper understanding of cavitation-related phenomena and liquid-assisted laser processing.